2020
DOI: 10.2147/dddt.s250991
|View full text |Cite
|
Sign up to set email alerts
|

<p>Network Pharmacology-Based Prediction and Verification of the Active Ingredients and Potential Targets of Zuojinwan for Treating Colorectal Cancer</p>

Abstract: Background: Zuojinwan (ZJW), a famous Chinese medicine formula, has been widely used to treat colorectal cancer (CRC). However, its bioactive compounds, potential targets, and molecular mechanism remain largely elusive. Aim: A network pharmacology-based strategy combined with molecular docking studies and in vitro validation were employed to investigate bioactive compounds, potential targets, and molecular mechanism of ZJW against CRC. Materials and Methods: Bioactive compounds and potential targets of ZJW, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 55 publications
0
51
0
Order By: Relevance
“… Adamson and Swenson, 2017 ; Channappanavar and Perlman, 2017 ; Das and Yu, 2012 ; Eijkelenboom and Burgering, 2013 ; Ferner and Aronson, 2020 ; Grimes and Grimes, 2020 ; BHolshue et al, 2020 ; Hou et al, 2016 ; Kanehisa and Sato, 2020 ; Kim and Choi, 2010 ; Lai et al, 2020 ; Tukaj and Węgrzyn, 2016 ; Wan et al, 2020 ; Wu and Yang, 2020 ; Zhang et al, 2020 , Cao et al, 2020 , Huang et al, 2020 , Luo et al, 2019 …”
Section: Uncited Referencesmentioning
confidence: 99%
“… Adamson and Swenson, 2017 ; Channappanavar and Perlman, 2017 ; Das and Yu, 2012 ; Eijkelenboom and Burgering, 2013 ; Ferner and Aronson, 2020 ; Grimes and Grimes, 2020 ; BHolshue et al, 2020 ; Hou et al, 2016 ; Kanehisa and Sato, 2020 ; Kim and Choi, 2010 ; Lai et al, 2020 ; Tukaj and Węgrzyn, 2016 ; Wan et al, 2020 ; Wu and Yang, 2020 ; Zhang et al, 2020 , Cao et al, 2020 , Huang et al, 2020 , Luo et al, 2019 …”
Section: Uncited Referencesmentioning
confidence: 99%
“…Previous studies have shown that ZJP mainly inhibits proliferation, induces cell apoptosis and autophagic cell death, and has certain anticancer effects on colon cancer, breast cancer, liver cancer, lung cancer, colorectal cancer, and other types of cancer. 27 In the current study, a total of 294 types of Chinese herbal medicines were identified, and 41 components were followed up using comprehensive retrieval methods in the Chinese herbal medicine database and the BATMAN-TCM database. In addition, 2969 pancreatic cancer-related genes were identified.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, ZJP significantly inhibited the proliferation of human tumor cell lines by inducing mitochondrial apoptosis and had significant inhibitory effects on HepG2-derived mouse tumors, breast cancer, colorectal cancer, and other cancers. [25][26][27] In recent years, biotechnology has made great progress. Network pharmacology based on large databases has become a powerful tool for studying TCM because it allows investigators to study the mechanism of action of compounds from the molecular level to the pathway level.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it provides a basic set of characteristics for data integration, analysis, and visualization for complicated network analysis. The key topological parameters (degree) characterize the most important nodes in the network; higher quantitative values of topological parameters indicate greater importance of the node [12]. GO enrichment analysis GO analysis was performed using the online functional annotation and enrichment tool DAVID (https://david.ncifcrf.gov/).…”
Section: Ppi Networkmentioning
confidence: 99%